Erosion of the Principle of Mutual Recognition. European Arrest Warrant and the Principle of Mutual Recognition in the Light of the Recent CJEU Rulings - Sakowicz, Andrzej (Review of European and Comparative Law, 2023)
An effective implementation of mutual recognition in the Area of Freedom, Security, and Justice requires mutual trust between the Member State. Mutual trust has been eroded in some Member States due to the rule of law crisis. However, it is not only the rule of law crisis, but also the departure of the Member States from the shared values of respect for fundamental rights, as well as the differences in the prosecutorial systems of individual Member States, that have caused changes in the perception of the principle of mutual recognition. This paper will examine the evolving approach to the principle of mutual recognition based on the recent Court of Justice of the European Union rulings on the European arrest warrant. The analysis concludes that the CJEU attaches more importance to the protection of the principle of mutual recognition, the prosecution of perpetrators of crime, and the unwavering presumption of respect for fundamental rights by the Member states than to the effective protection of fundamental rights.